2018
DOI: 10.1093/gerona/gly273
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sphingolipids and Cardiopulmonary Fitness in Coronary Artery Disease Patients Undertaking Cardiac Rehabilitation

Abstract: The long-term benefits conferred by cardiac rehabilitation (CR) in those with coronary artery disease (CAD) are strongly linked with an improvement in cardiopulmonary fitness. This study aimed to determine the association between peripheral sphingolipids and cardiopulmonary fitness in CAD subjects undertaking CR. Patients with CAD (n = 100, mean age = 64 ± 6 years, 85% male, mean years of education = 17 ± 3 years) underwent 6 months of CR with blood collected at baseline, 3 and 6 months. Cardiopulmonary fitnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…In particular, SMs with saturated acyl chains (C18:0 to C24:0) were closely correlated with parameters of obesity or insulin resistance [ 46 ]. As is consistent with our results, previous studies reported negative correlations between CRF and blood SM C18:0 [ 22 , 47 ] or SM C18:1 [ 20 , 47 ] in young [ 22 ] and middle-aged [ 20 ] adults or patients with coronary artery disease [ 47 ]. Despite sex-related differences, our findings indicate that even in healthy individuals and across a broad age range, higher CRF tends to be associated with lower values of potential novel blood biomarkers of the pathophysiological processes underlying cardiometabolic diseases.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, SMs with saturated acyl chains (C18:0 to C24:0) were closely correlated with parameters of obesity or insulin resistance [ 46 ]. As is consistent with our results, previous studies reported negative correlations between CRF and blood SM C18:0 [ 22 , 47 ] or SM C18:1 [ 20 , 47 ] in young [ 22 ] and middle-aged [ 20 ] adults or patients with coronary artery disease [ 47 ]. Despite sex-related differences, our findings indicate that even in healthy individuals and across a broad age range, higher CRF tends to be associated with lower values of potential novel blood biomarkers of the pathophysiological processes underlying cardiometabolic diseases.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, specific plasma ceramides, namely d18:1/C16:0-, d18:1/C18:0- and d18:1/C24:1-ceramide, appear to be indicative of plaque instability and CVD fatality. 8 104 105 106 These ceramide species predict cardiovascular events in asymptomatic individuals 78 . Calculation of the ratio of d18:1/C16:0-ceramide to d18:1/C24:0-ceramide significantly improved CAD prediction.…”
Section: Sls As Cvd Biomarkersmentioning
confidence: 99%
“…Thus, the American Heart Association even recommends assessing CRF as a vital sign in clinical practice [97]. Strikingly, several ceramide species were reported to be negatively associated with CRF: Cer (18:0;2/22:1) [103], Cer (18:0;2/24:1) [103], Cer (18:1;2/14:0) [103], Cer (18:1;2/16:0) [103][104][105], Cer (18:1;2/18:0) [105,106], Cer (18:1;2/20:0) [105,106], Cer (18:1;2/22:1) [103] and Cer (18:1;2/24:1) [105]. The three cardiometabolically deleterious ceramide species clinically used in the ceramide-phospholipid score (Cer (18:1;2/16:0), Cer (18:1;2/18:0) and Cer (18:1;2/24:1)) were notably reported to be negatively associated with CRF [12,79].…”
Section: Exercise-a Modulator Of Ceramide Levelsmentioning
confidence: 99%